2023
DOI: 10.20944/preprints202308.2159.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Good Hygiene Practice on Board Vessels for Fish Quality and Safety

Pierina Visciano

Abstract: Fish and fish products are very appreciated in the human diet because of high quality proteins and other important nutrients, such as minerals and polyunsaturated fatty acids. Maintaining freshness, quality and safety is essential in the fish supply chain, starting from on board vessels where the product must be carefully checked and protected from any source of contamination. Safe fishing and handling of fish are very important to reduce the risk of foodborne diseases caused by pathogenic microorganisms such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Mendoza, Aquino, and Reyes [ 30 ] found enterococci in their tilapia samples at an average level of 1.89 x10 7 cfu/g, while Çardak et al [ 13 ] observed the presence of enterococci ranging from 1.0 to 2.5-log cfu/g in less than 10% of the analyzed raw and processed seafood samples. Higher contamination of raw materials with enterococci may result from contamination during evisceration due to poor personal hygiene, poor processing hygiene, or poor water quality [ 13 , 31 ]. Processing technologies (freezing and smoking) can reduce the bacterial load of food [ 32 ], as observed in this study ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mendoza, Aquino, and Reyes [ 30 ] found enterococci in their tilapia samples at an average level of 1.89 x10 7 cfu/g, while Çardak et al [ 13 ] observed the presence of enterococci ranging from 1.0 to 2.5-log cfu/g in less than 10% of the analyzed raw and processed seafood samples. Higher contamination of raw materials with enterococci may result from contamination during evisceration due to poor personal hygiene, poor processing hygiene, or poor water quality [ 13 , 31 ]. Processing technologies (freezing and smoking) can reduce the bacterial load of food [ 32 ], as observed in this study ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%